(untitled) (International journal of artificial intelligence, 2025)
Wind power is one of the fastest-growing renewable energy sectors, but its overall performance depends heavily on aerodynamic design. This paper discusses methods to enhance the aerodynamic efficiency of wind turbines through blade optimization, active flow control, and adaptive pitch regulation systems.